Persepsi Mahasiswa Ilmu Politik Angkatan 2021 Terhadap Jalan Alternative Batubara Yang di Janjikan Oleh Gubernur Jambi - Lidia Murni Saruksuk; Lyany Cristin Banurea; Desi Rotua Simbolon; Hesekiel Sihombing (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Coal in Jambi is a problem that people continually complain about and causes traffic jams and damaged roads. Until the end of 2022, there are 51 coal mining companies operating in Jambi Province, spread across Sarolangun, Tebo, Batanghari and Muaro Jambi. The Jambi provincial government is preparing alternative coal transportation routes via land and water. This research uses quantitative research with a descriptive format, aimed at explaining, summarizing various conditions, various situations or various variables that arise in the community which is the object of the research based on what happens. Then bring to the surface the character or description of the condition, situation or variable. The results of observations from questionnaires that have been distributed by students hope that this alternative will reduce the level of traffic jams and the number of accidents that occur in the community. The Governor of Jambi, Al Haris, has made various efforts in alternative development in his province. Students hope that this alternative will reduce the level of traffic jams and accidents that occur in society. The Governor of Jambi, Al Haris, has made various efforts in alternative development in his province. One of them is controlling the use of coal transport vehicle plates to repair roads. Apart from that, the provincial government is also discussing the issue of coal transport and the construction of special roads for coal transport. The Governor also admits that his authority is limited in matters of coal transport, but various efforts have been made. carried out, including opening alternative roads and giving lambuk numbers to coal transport. Apart from that, Governor Al Haris also stated the ban on coal transport via national roads and the importance of the progress of Jambi City as a barometer for the development of Jambi province. However, despite this, we can also feel that currently the accident rate is still there.